Becoming Monument, Activating Windsor - Karen Engle (Societies, 2013)
What does it mean to live in a dying place? This auto-critical article asks this question in the context of the Windsor/Detroit region, one of the most economically depressed zones in North America. Using the work of Barthes, Benjamin, and Taussig, I ruminate on the psycho-somatic experiences of trying to navigate a world that most writers have already dismissed as haunted and abandoned.